A PSF-based approach to Kepler/K2 data – III. Search for exoplanets and variable stars within the open cluster M 67 (NGC 2682). Issue 2 (26th August 2016) - Nardiello, D.; Libralato, M.; Bedin, L. R.; Piotto, G.; Borsato, L.; Granata, V.; Malavolta, L.; Nascimbeni, V.
Abstract: In the third paper of this series we continue the exploitation of Kepler/K2 data in dense stellar fields using our PSF-based method. This work is focused on a ∼720-arcmin 2 region centred on the Solar-metallicity and Solar-age open cluster M 67. We extracted light curves for all detectable sources in the Kepler channels 13 and 14, adopting our technique based on the usage of a high-angular-resolution input catalogue and target-neighbour subtraction. We detrended light curves for systematic errors, and searched for variables and exoplanets using several tools. We found 451 variables, of which 299 are new detection. Three planetary candidates were detected by our pipeline in this field. Raw and detrended light curves, catalogues, and K2 stacked images used in this work will be released to the community.